2022
DOI: 10.3389/fgene.2022.838021
|View full text |Cite
|
Sign up to set email alerts
|

Prognostication of Pancreatic Cancer Using The Cancer Genome Atlas Based Ferroptosis-Related Long Non-Coding RNAs

Abstract: Background: Long non-coding RNAs (lncRNAs) are key regulators of pancreatic cancer development and are involved in ferroptosis regulation. LncRNA transcript levels serve as a prognostic factor for pancreatic cancer. Therefore, identifying ferroptosis-related lncRNAs (FRLs) with prognostic value in pancreatic cancer is critical.Methods: In this study, FRLs were identified by combining The Cancer Genome Atlas (TCGA) and FerrDb databases. For training cohort, univariate Cox, Lasso, and multivariate Cox regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…e mechanism of cell death varies. Apoptosis [18], pyroptosis [19], necrosis [20], and ferroptosis [21][22][23] are the most commonly observed. Recently, Tsvetkov et al found a copper-based mechanism that was completely different from the known mechanisms of cell death, and they named it "cuproptosis" [7].…”
Section: Discussionmentioning
confidence: 99%
“…e mechanism of cell death varies. Apoptosis [18], pyroptosis [19], necrosis [20], and ferroptosis [21][22][23] are the most commonly observed. Recently, Tsvetkov et al found a copper-based mechanism that was completely different from the known mechanisms of cell death, and they named it "cuproptosis" [7].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the expression levels of MIR193BHG and HOOK3 showed significant differences between the two groups. Previous studies have identified MIR193BHG as a prognostic marker in pancreatic, ovarian, and head and neck squamous cell carcinoma (48)(49)(50). Additionally, MIR193BHG might play a pivotal role in preeclampsia related to blood pressure and urine protein and could be a potential prognostic biomarker in early-onset preeclampsia (51,52).…”
Section: Discussionmentioning
confidence: 98%
“…were identi ed as lncRNAs associated with cuproptosis, pyroptosis, and ferroptosis, respectively, and showed promising prognostic evaluation characteristics [29][30][31]. Previous research has shown that TDRKH-AS1 promotes tumorigenesis by activating the Wnt pathway in colorectal cancer, and its high expression is associated with poor prognosis in colorectal cancer patients [32].…”
Section: Discussionmentioning
confidence: 99%